1999
DOI: 10.1143/jjap.38.2092
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of PtO and α-PtO2 Thin Films by Reactive Sputtering and Their Electrical Properties

Abstract: Pt oxide thin films are prepared by sputtering Pt target in an atmosphere containing Ar and O2 gases. Polycrystalline PtO and α-PtO2 films are obtained in O2 flow ratio regions of 30–50% and 80–100%, respectively, at a substrate temperature of 300°C. Electrical resistivity of the PtO film is found to be 1–2 mΩcm and shows almost no temperature dependence. The metallic character of the PtO film is assumed to be suppressed by its poor crystallinity. The α-PtO2 film has a la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(59 citation statements)
references
References 21 publications
2
57
0
Order By: Relevance
“…On the other hand, the spectrum peaks of the Pt oxide thin films prepared by sputtering in Ar -50% O 2 and 100% O 2 were 72.1 and 74.6 eV, respectively. The former corresponds to approximately the binding energy of 72.3 eV for PtO and the latter can be assigned to that of 74.4 eV for PtO 2 , which were reported by Abe et al [6] It is concluded from the EPMA and XPS analysis results that we can prepare the metallic Pt and two kinds of Pt oxide thin films, PtO and PtO 2 , by changing the composition of the reactive gas. Figure 5 shows the first anodic polarization curves of Pt thin film prepared using 100% Ar.…”
Section: Experimental 21 Preparation Of Sample Filmsupporting
confidence: 60%
“…On the other hand, the spectrum peaks of the Pt oxide thin films prepared by sputtering in Ar -50% O 2 and 100% O 2 were 72.1 and 74.6 eV, respectively. The former corresponds to approximately the binding energy of 72.3 eV for PtO and the latter can be assigned to that of 74.4 eV for PtO 2 , which were reported by Abe et al [6] It is concluded from the EPMA and XPS analysis results that we can prepare the metallic Pt and two kinds of Pt oxide thin films, PtO and PtO 2 , by changing the composition of the reactive gas. Figure 5 shows the first anodic polarization curves of Pt thin film prepared using 100% Ar.…”
Section: Experimental 21 Preparation Of Sample Filmsupporting
confidence: 60%
“…For the process employing Pt͑acac͒ 2 and O 3 , a lower resistivity ͑1.5-5 ⍀ cm͒ was reported most probably due to a lower O content ͑PtO 1.6 ͒. 13,20 The Table I. The starting substrate at 0 cycles was Si͑100͒ with 400 nm SiO 2 .…”
Section: Resultsmentioning
confidence: 99%
“…The former peak was attributed to the binding energy of 71.3 eV for metallic Pt and the latter was close to the binding energy of 72.3 eV for PtO. 10,15,16) In addition, the latter intensity was considerably weaker than the former one. Therefore, it was estimated that the thin film produced in the 100% Ar plasma was primarily composed of metallic Pt.…”
Section: Co Stripping Voltammetrymentioning
confidence: 74%
“…The peaks of 71.99 and 73.89 eV were attributed to PtO and PtO 2 , respectively. 15,16) Moreover, the peak of 73.89 eV was fairly larger than that of 71.99 eV.…”
Section: Co Stripping Voltammetrymentioning
confidence: 91%